Critical reflections on Water-Energy-Food Nexus in Computable General Equilibrium models: A systematic literature review. (November 2021) - Bardazzi, Elisa; Bosello, Francesco
Abstract: The paper analyses how the Water-Energy-Food Nexus is treated in Computable General Equilibrium (CGE) models, discussing their design, importance and possible ways of improvement. The analysis of their structure is critical for evaluating their potential efficiency in understanding the Nexus, which will be particularly effective for gauging the importance of the topic, the reciprocal dependency of its elements and the expected macroeconomic, demographic and climatic pressures that will act on its components. General equilibrium models can be useful devices to this end, as they are specifically built to track interdependencies and transmission effects across sectors and countries. Nevertheless, the review showed that most CGEs in the literature struggle to represent the competing water uses across sectors and, in particular, those concerning the energy sector. Therefore, it highlights the need to resolve this issue as a necessary step toward improving future research. Highlights: The Water-Energy-Food Nexus modelling is a complex and critical issue. CGEs are relevant in addressing sectoral interactions and macroeconomic impacts. Water uses of energy sector is critical for macroeconomic implication of the nexus. Water endowment modelling for the energy sector in CGEs is still at an early stage.